UMP to restore Terenang Ceramic, the heritage of Pahang - Siti Sarah, Mohamad Rajimi (2017)
Kuantan, 19th April – Not many of us know the existence of Terenang Ceramic, a pottery used to store water in the olden days. It is believed to have its origin from Pasir Durian Village in Kuala Tembeling, located an hour drive to Jerantut, Pahang.